Advances in Immune Monitoring Approaches for Sepsis-Induced Immunosuppression - Yao, Ren-Qi; Ren, Chao; Zheng, Li-Yu; Xia, Zhao-Fan; Yao, Yong-Ming (Frontiers in Immunology, 2022)
Sepsis represents a life-threatening organ dysfunction due to an aberrant host response. Of note, majority of patients have experienced a severe immune depression during and after sepsis, which is significantly correlated with the occurrence of nosocomial infection and higher risk of in-hospital death. Nevertheless, clinical sign of sepsis-induced immune paralysis remains highly indetectable and ambiguous. Given that, specific yet robust biomarkers for monitoring immune functional status of septic patients are of prominent significance in clinical practice. In turn, stratification of a subgroup of septic patients with immunosuppressive state will greatly contribute to the implementation of personalized adjuvant immunotherapy. In this review, we comprehensively summarize the mechanism of sepsis-associated immunosuppression at cellular level and highlight the recent advances in immune monitoring approaches targeting functional status of both innate and adaptive immune responses.